Longitudinal associations between relative deprivation and non-suicidal self-injury in early adolescents: a moderated mediation model - Chang Wei; Bao Liu; Xiaojing An; Yu Wang (Frontiers in Psychiatry)
IntroductionRelative deprivation is associated with non-suicidal self-injury; however, the mechanisms underlying this association have been largely unexplored. Based on relative deprivation theory, the functional model of non-suicidal self-injury, and the organism-environment interaction model, the current study examined the mediating role of emotional symptoms and moderating role of deviant peer affiliation to determine how and when relative deprivation is associated with non-suicidal self-injury.MethodsParticipants were 601 Chinese early adolescents who completed self-report scales measuring relative deprivation, emotional symptoms, non-suicidal self-injury, and deviant peer affiliation at three time points over the course of 12 months.ResultsThe results showed that relative deprivation at Wave 1 was positively associated with non-suicidal self-injury at Wave 3, and emotional symptoms at Wave 2 fully mediated this association. Furthermore, deviant peer affiliation at Wave 3 moderated the pathway from emotional symptoms to subsequent non-suicidal self-injury in the mediated model. Specifically, emotional symptoms significantly predicted an increase in non-suicidal self-injury but only in early adolescents with high deviant peer affiliation.ConclusionsOur findings can encourage educators to consider the interaction between individual and peer factors when providing interventions for early adolescents who engage in non-suicidal self-injury.